“They rape us and they kill us”: Feminicidal violence and institutional neglect in the experiences of girls and adolescents in social care centers in Jalisco, Mexico - Gabriela Sánchez López; Rosa Elena Sandoval Zapata; Michelle Mir Trejo; Ana Cristina Skinfield Vértiz; María de los Ángeles Téllez Flores; Mónica Michelle Rojas Medina (Salud Colectiva)
This article examines the continuum of feminicidal violence and its connection to protection systems in Mexico from the perspective of girls and adolescents. Based on a qualitative study conducted between 2022 and 2024 in two social care centers — one public and one private — it analyzes the experiences of 31 girls and adolescents who have gone through this cycle of violence. Through in-depth interviews, body mapping, and ethnographic observation, the study reveals that the violence rooted in their communities of origin does not cease upon entering the social care centers; instead, it is transformed into new forms of institutional control and violence. Their narratives reveal a continuity of violence that constitutes a web of dispossession and dehumanization, in which institutionalization does not represent a refuge but rather an extension of the same system of oppression. The findings show that social care centers do not break the cycle of previous violence, but rather form part of the same continuum of control, exclusion, and the precarization of life, becoming embedded within the broader framework of impunity upheld by the state.